STRATIGRAPHY AS GEOCHRONOMETRY - Popov A.V. (My University, 2002)
The present development of stratigraphic methods, especially of zonal stratigraphy, necessitates usage of a correct measurement procedure in stratigraphic investigations. Such a procedure should be based on the independent external metering system, e.g., on the Golovkinskii principle. An important component of stratigraphic investigations, all efforts are ultimately aimed at, is the establishment of boundary stratotypes. The main and single goal of stratigraphy is to elucidate the geological time structure. The most complete reconstruction of geological processes in time and space is achieved by geological mapping that represents, together with stratigraphic investigations, an integral method of graphic modeling of geological development in a form of geological map.